A single-molecule conductance study on the rotational isomers of a hexaarylbenzene derivative carrying dipolar rotating units. (1st October 2021) - Miyazaki, Takuya; Shoji, Yoshiaki; Fujii, Shintaro; Fukushima, Takanori
Abstract: Using a scanning tunneling microscopy-break junction (STM-BJ) technique, we evaluated the single-molecule conductance of stable but interconvertible two rotational isomers of a hexaarylbenzene derivative featuring dipolar rotatable difluorophenyl units and tripodal thiol groups. The STM-BJ measurements of a configuration of single-molecule junction, formed between a Au-STM tip and a Au(111)/mica substrate covered with the hexaarylbenzene molecule, showed that the conductance behaviors of the rotational isomers are different from one another. This result takes a step forward in our goal of developing single-molecule switching/memory systems driven by electric fields.